Multi-Agent system Adaptation for Feature Driven Development Methodology - Khamisa A. Yousef; Huweida A. Darbi (African Journal of Advanced Pure and Applied Sciences, 2025)
This paper presents the integration of Multi-Agent Systems (MAS) with Feature-Driven Development (FDD) methodology, which is an agile methodology that emphasizes client-valued features through well-defined stages. Despite its modularity and scalability, traditional FDD implementations often come down to flexibility and autonomous coordination in complex environments. The paper offers a conceptual model that illustrates how agents interact and align with FDD processes, presenting a new approach to improving flexibility and productivity in software development. The synergy between MAS and FDD can improve prototyping, automate jobs, and expedite requirement collection, leading to higher-quality software and better stakeholder alignment, and ultimately, more successful software projects.